3D techniques and fossil identification: An elephant shrew hemi-mandible from the Malapa site - Aurore Val; Kristian Carlson; Christine Steininger; Job Kibii; Cecil Churms; Brian Kuhn; Lee Berger (South African Journal of Science)
Conventional methods for extracting fossilised bones from calcified clastic sediments, using air drills or chemical preparations, can damage specimens to the point of rendering them unidentifiable. As an alternative, we tested an in silico approach that extended preparation and identification possibilities beyond those realisable using physical methods, ultimately proving to be crucial in identifying a fragile fossil. Image data from a matrix-encased hemi-mandible of a micromammal that was collected from the Plio-Pleistocene site of Malapa, Cradle of Humankind, South Africa, were acquired using microtomography. From the resultant images, a 3D rendering of the fossil was digitally segmented. Diagnostic morphologies were evaluated on the rendering for comparison with extant comparative specimens, positively identifying the specimen as an elephant shrew (Elephantulus sp.). This specimen is the first positively identified micromammal in the Malapa faunal assemblage. Cutting-edge in silico preparation technology provides a novel tool for identifying fossils without endangering bone integrity, as is commonly risked with physical preparation.